0443 Life Values Expressed by Female Veterans Engaged in an Acceptance and Commitment-based Behavioral Therapy for Primary Insomnia. (25th May 2022) - Saldaña, Kathryn; Revolorio, Kaddy; Carlson, Gwendolyn; Culver, Najwa; Kay, Morgan; McGowen, Sarah Kate; Song, Yeonsu; Martin, Jennifer
Abstract: Introduction: Women Veterans disproportionately suffer from insomnia, which negatively impacts health and overall quality of life. Insomnia can result in fewer value-based choices and less engagement in meaningful life activities. This study sought to identify common life values expressed by women Veterans engaged in an acceptance-and commitment-based behavioral therapy for primary insomnia. Methods: 74 female-identifying Veterans (mean age=48.3 years; 47.3% non-Hispanic White, 28.4% Black/African American, 23.0% Hispanic/Latina, 12.2% American Indian/Alaska Native, 5.4% Asian American and 9.5% Other) who met DSM-5 diagnostic criteria for Insomnia disorder were randomly assigned to an acceptance-based behavioral treatment for insomnia called Acceptance of the Behavioral Changes to treat insomnia (ABC-I; compared to a similarly structured group receiving CBT-I). Women in the ABC-I group received 5 weekly, 60-minute sessions containing key components of sleep restriction, stimulus control, and sleep hygiene. In place of traditional cognitive therapy exercises, we incorporated essential components of Acceptance and Commitment Therapy (ACT), such as the identification of values. Outcome measures included qualitative responses of values identified by participants. Qualitative responses were coded by three separate raters who coded participant stated values into five categories: Work/Education, Relationships, Personal Care/Health, Leisure, and Pets. Results: The three independent coders reached 100% agreement after independent coding and adjudication. The five categories are listed in order of frequency of response: 1) Relationships (n =68); 2) Personal Care/Health (n =51); 3) Work/Education (n =46); 4) Pets (n =12) and; 5) Leisure (n =5). Conclusion: The current study showed that personal and social relationships are of high importance to women Veterans undergoing behavioral treatment for insomnia, followed by personal care and health, which includes spirituality/religion, and physical and mental health. Findings indicate that incorporating outcomes of insomnia treatment trials that assess relationship quality may prove important in future studies of women Veterans with sleep disorders. Further, identifying common shared values among women Veterans is an important first step in developing and adapting treatments for insomnia that help to improve quality of life. Support (If Any): VA HSR&D IIR 13-058-2 and RCS-20-191, NIH K24 HL143055; VA GLAHS GRECC